Two case studies of the treatment of simple onycholysis with disappearing nail bed caused by trauma by combined pharmacological, orthonyxia and taping methods - Adamczyk, Katarzyna; Garncarczyk, Agnieszka; Wcisło‐Dziadecka, Dominika (Journal of cosmetic dermatology, 2023)
Simple onycholysis is a common complaint after trauma and consists in separation of the nail plate from the nail bed. If untreated, prolonged onycholysis may cause a disappearing nail bed (DNB) that leads to the shortening or narrowing of the nail plate. This study is aimed at discussing possible treatment of chronic simple onycholysis with DNB by combined conservative methods. Simple onycholysis and DNB treatment consists of Onygen® cream application, nail bed massages, bracing procedures and nail folds taping with kinesio tape. Long-lasting simple onycholysis with DNB may be fully eliminated by applying the combined pharmacological, orthonyxia and taping treatment. Advanced simple onycholysis, which leads to the DNB and, in consequence, to the shortening or narrowing of the nail plate, causes cosmetic discomfort for patients. A damaged nail apparatus is also more susceptible to new traumas. Even long-standing onycholysis with DNB can be successfully treated with easy-to-apply conservative methods. The key point of therapy is the use of several methods of treatment with different effects on the nail apparatus. The effects of described therapy are highly satisfactory, the only drawback being its long term, which is caused by slow growth of the nails.